Distribution and Speciation of Selenium, Antimony, and Arsenic in Soils and Sediments Around the Area of Xikuangshan (China). Issue 11 (11th August 2016) - Yang, Hailin; He, Mengchang
Abstract : Selenium (Se), antimony (Sb), and arsenic (As) throughout the world naturally or anthropogenically in the environment are of great concern. In this study, the distribution and speciation of Se, Sb, and As in four types of environmental matrices (paddy soils, dry‐land soils, soil profiles, and sediments) from an antimony mine area were investigated. Significant correlations between the total Se and Sb and As contents were observed, which, in association with the geochemical fractions and species, may help predict the distribution and availability of these metalloids in mining/smelting‐impacted soils and sediments. The maximum Se, Sb, and As concentrations were found in the sediments, where a significant decrease in the soluble and exchangeable fractions and an increase in the residual fraction were observed with an increasing distance from the river's headstream. In the environment, Se, Sb, and As are commonly present as either Se(IV), Se(VI), Sb(III), Sb(V), As(III), or As(V). These inorganic forms of Se, Sb, and As, as well as methylated forms, are subject to various biogeochemical processes with natural components, such as organic matter and mineral phases. Because of the toxicity and persistency of metalloids, a better understanding of Se, Sb, and As speciation is crucial for predicting and protecting environmental health. Abstract : Mining and smelting activities contribute to metalloid pollution to the environment in large amounts. The systematic investigation of Se species distribution in long‐term Sb‐ and As‐exposed regions is analyzed here. Experimental evidence suggests that the highest Se concentrations found in sediment environment presents a potential risk of recontamination.